Modelling VLE data of CO2 and H2S in aqueous solutions of N-methyldiethanolamine based on non-random mixing rules. (November 2015) - Poormohammadian, S.J.; Lashanizadegan, Asghar; Salooki, Mahdi Koolivand
Graphical abstract: Highlights: We simulated the VLE data of CO2 and H2 S in MDEA solutions with two parameter EOS. Random mixing rules have not worked well for this simulation. Adding binary interaction parameters ( k ij ) gives more deviations from experimental data. Non-random mixing rules are well-suited for the modelling of these systems. We compared our modelling results to results of e-NRTL, ePC-SAFT and UNIQUAC models. Abstract: The vapor liquid equilibrium (VLE) data of carbon dioxide and hydrogen sulfide in N-methyldiethanolamine (MDEA) solutions has been investigated by Peng–Robinson and Soave–Redlish–Kwong equations of state (EOS). Random and non-random mixing rules have been used for calculating the parameters of the EOS. The predictions of the modelling are compared with the experimental data obtained from the literature for 2 and 4 mole of MDEA per kg of water. It was shown that the data obtained by random mixing rules has 24.7 and 32.5% absolute relative deviation (ARD) for PR and SRK equations of state respectively in calculating the partial pressure of CO2 . Also the results had more deviation from the experimental data when binary interaction parameters ( k ij ) added to the random mixing rules. Finally the VLE data of CO2 and H2 S is examined by non-random mixing rules and the results were in excellent agreement with the experimental data. The ARD in this case was 3.7 and 6.7% for PR and SRK equations of states respectively in calculating the partial pressure of H2 S. The results of the modelling have been compared and discussed with other modelling results such as ePC-SAFC, eNRTL and UNIQUAC models.